Features of Extracranial Hemodynamics in Children with Bronchial Asthma - S.M. Nedelska; O.Yu Akulova (Zaslavsky O.Yu., 2014)
The paper analyzes the performance of extracranial hemodynamics - volumetric and linear blood flow velocity, the state of peripheral vascular resistance and vascular reactivity at ultrasound Doppler examination of the internal carotid and vertebral arteries of 66 children with bronchial asthma and and 22 healthy children. Development of regional hypoperfusion in vertebrobasilar zone, disorders of the carotid system are proven, but these changes have not led to a decrease in the volumetric blood flow velocity in both internal carotid arteries and the total volume of cerebral blood flow, indicating the compensation of hemodynamic disturbances due to the influence of constant rates in volumetric blood flow in the carotid system. Changes in parameters of extracranial hemodynamics in children with bronchial asthma should be considered as predictor of cerebrovascular complications in this group of patients.